Blood transfusion for severe anaemia in children in a Kenyan hospital. - English, M; Ahmed, M; Ngando, C; Berkley, J; Ross, A (2002)
Severe anaemia often secondary to malaria is a major contributor to child mortality in sub-Saharan Africa. We have confirmed that use of simple clinical and laboratory criteria can identify those children likely to benefit most from treatment. We have also shown that the speed of response may be critical. The quality and capacity of blood transfusion services could therefore have a major, direct effect on inpatient child mortality.